Doença de Alzheimer: estudo por docagem molecular entre o Clorpirifós e a proteína Tau - Neves, Bruno Blaszczyk (2021)
According to data from the WHO and ALZ.ORG, more than 50 million people worldwide have Alzheimer’s disease (AD), a dysfunction of memory and other cognitive domains that lead to death within 3 to 9 years after diagnosis. AD is the most common form of dementia, represented by 70% of cases in autopsies and clinical series. As such, the seventh largest cause of death in the world. The main risk factor for Alzheimer’s disease is age. 1275 new cases are diagnosed annually for every 100,000 people over 65 in the world; and the chances of receiving a diagnosis of the disease after the age of 85 years exceeds one in three. In Brazil, according to the Brazilian Alzheimer’s Association (Abraz), there are more than 1.2 million cases, and the number will double by 2030. Molecular damage was detected in Alzheimer’s disease, which generates an accumulation of folded proteins in the aging brain, resulting in oxidative and inflammatory damage, which in turn lead to energy failure and synaptic dysfunction. Within this line of thought, the Beta-Amyloid Hypothesis (βA) and Tau Entanglement Hypothesis stand out, also called Neurofibrillary tangles – ENF. AD development is drastically influenced by diet and studies reveal the link between pesticides and neurological problems. However, correlating pesticides and ENF, little information was found, one of those responsible for AD and one of the main markers to prove postmortem disease through necropsy. Chlorpyrifos is an organophosphate (OP) used primarily as an insecticide. Compounds Ofs have a high stability of bonds between oxygen and phosphorus atoms and are commonly associated by the inhibition of the enzyme acetylcholinesterase (AchE), which generates their high toxicity. The aim of this study was to evaluate, in syphilic, the toxicological effects of the Chlorpyrifos molecule against the interaction of tau protein and the binding site of its macromolecule and the formation of NSF. Thus, seeking to understand the possible relationship with the development of AD. The in-sy method of molecular docking provided by LNCC DockThor was used. By using the program and applying the blind coupling docking strategy, two binding sites were found in the tau protein. Both with affinity for Chlorpyrifos (CPF), and one with its metabolite, Chlorpyrifos-Oxon (CPF-O). The best poses obtained results of total energy and binding distance of: CPF-O (-)20,271 kcal∙mol-1 and two hydrogen bonds one of 1.80 Å and the other of 2.78 Å; CPF (-)17,472 kcal∙mol-1 and a hydrogen bond of 2.56 Å.